# [Discrete Math] Direct Proof with multiple variables?

O stands for odd and E stands for even, so for example O(x) = x is odd.

Problem:

O(l) ∧ (E(m^2) ∨ E(l)) ∧ (O(m^2) ∨ E(n+3)) -> O(2n+7)

I know I start by assuming that the first part is true, but I'm completely lost on what to do next. The multiple variables are throwing me off and I have no idea which identities or laws I should be using. Do I separate E(n+3) by simplification first? What do I do with the rest?

There are no answers yet.

Be the first to answer this question.

Be the first to answer this question.